Selective sensing of pyrophosphate in physiological media using zinc(ii)dipicolylamino-functionalised peptides1. Issue 28 (28th July 2015) - Zwicker, Vincent E.; Long, Benjamin M.; Jolliffe, Katrina A.
<x xml:space="preserve">Abstract</x> Linear zinc(ii)dipicolylamino-functionalised peptides show high affinity and selectivity for pyrophosphate in physiological media.